The impact of digital game-based learning towards Arabic language communication - Mohammad Taufiq Abdul Ghani,; Wan Ab Aziz Wan Daud, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The digital game-based learning has the potential to enable new forms of learning concept which could enhance student’s communication. Therefore, this study aims to determine the impact of digital game-based learning on students’ communication performance. Participants were 611 non-Arabic students enrolled in an Arabic language course. This study uses a quasi-experimental design. The students were chosen through a random sampling technique to be part of the control group and treatment group. Pre-test and post-test were used to assess the students’ performance before and after the digital game-based learning intervention. The intervention took place over a period of four weeks in which students in the treatment group used educational digital games during Arabic language class. On the other hand, students in the control group underwent the traditional Arabic language instruction. At the end of the intervention, several students were selected through purposive sampling technique to participate in a semi-structured interview. The result found that students in the treatment group were significantly outperformed in Arabic communication knowledge compared to the control group and the digital game-based learning affected many aspects of their communication performance. In addition to this, the students demonstrate a favorable acceptance of practising Arabic communication through educational digital games, which helps them to grow their self-confidence, polish their critical thinking, and improve their learning environment.